What can traditional Chinese medicine do for adult neurogenesis? - Shen, Wei; Jiang, Ning; Zhou, Wenxia (Frontiers in Neuroscience, 2023)
Adult neurogenesis plays a crucial role in cognitive functions, as well as the regulation of mood, whereas aberrant adult neurogenesis contributes to various neurological and mental diseases. With the understanding of the significance of adult neurogenesis, the demand for improving adult neurogenesis is increasing. More and more researches have shown that traditional Chinese medicine (TCM), including TCM prescriptions (TCMPs), Chinese herbal medicine, and bioactive components, has unique advantages in treating neurological and mental diseases by regulating adult neurogenesis in multiple stages, including proliferation, differentiation, and maturation. In this review, we summarize the progress of TCM in improving adult neurogenesis，as well as the key possible mechanisms by which TCM may improve adult neurogenesis. Finally, we propose the possible strategies of TCM to improve adult neurogenesis in the treatment of neuropsychiatric diseases.